2005
DOI: 10.1002/sim.2201
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian decision procedures for dose‐escalation based on evidence of undesirable events and therapeutic benefit

Abstract: In this paper, Bayesian decision procedures are developed for dose-escalation studies based on bivariate observations of undesirable events and signs of therapeutic benefit. The methods generalize earlier approaches taking into account only the undesirable outcomes. Logistic regression models are used to model the two responses, which are both assumed to take a binary form. A prior distribution for the unknown model parameters is suggested and an optional safety constraint can be included. Gain functions to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…In other settings, different pharmacodynamic endpoints might be used. Whitehead et al (2006b) of an E max model: conservative in the sense that higher doses will appear more dangerous under the quadratic model and will thus be avoided until sufficient evidence of their safety has been collected. The authors recognise that each clinical study is unique, and that the details of other trials may be different from that studied here.…”
Section: Discussionmentioning
confidence: 99%
“…In other settings, different pharmacodynamic endpoints might be used. Whitehead et al (2006b) of an E max model: conservative in the sense that higher doses will appear more dangerous under the quadratic model and will thus be avoided until sufficient evidence of their safety has been collected. The authors recognise that each clinical study is unique, and that the details of other trials may be different from that studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant information in bioassay can be incorporated in a semi-parametric model [427]. Dose-finding designs accounted for two endpoints using utilities [428,429] and Bayesian designs for dose-escalation studies in healthy volunteers were compared [430]. Bayesian phase II designs were compared to Simon two-stage designs [431].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Therefore, in this paper, we extend the Bayesian approach of Whitehead et al [15,16] so that the bivariate outcomes are binary DLEs and continuous DOs. In doing so, we introduce an allowance for the correlations between repeated observations of DOs on the same subject, although we have not been able to do the same for the binary DLEs.…”
Section: Introductionmentioning
confidence: 97%
“…Whitehead et al [15] considered dose-escalation studies in which two responses are observed on each subject. One of these was referred to as a dose limiting event (DLE), and the other as a DO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation